Application of legume cover crop and various vermicompost dosages on young cinchona in the marginal area - Yudithia Maxiselly; Mira Ariyanti; Mochamad Arief Soleh; Naufal Fikri (Kultivasi, 2022)
AbstractCinchona (Cinchona ledgeriana Moens) is one of the important medicinal plants that have the potential to cultivate as herbal medicine. This plant grows well in highland areas. Developing cinchona plants in the marginal area needs effort and modification techniques such as planting legume cover crop (LCC) to maintain the humidity and supply nutrition by fertilizing. Vermicompost is one of the organic fertilizers with rich nutrition to support plant growth. This research aimed to observe the effect of a combination of Mucuna bracteata as LCC and vermicompost dosage on young cinchona growth in a marginal area. This research was carried out from September 2019 to March 2020 at the Ciparanje Experimental Station, Faculty of Agriculture, Universitas Padjadjaran. The experimental research was conducted using a Randomized Block Design (RBD) method, which consisted of 12 treatments which were a combination of legume cover crop (Mucuna bracteata) and vermicompost dosages (0 g, 200 g, 400 g, 600 g, 800 g, and 1000 g per plant), with four replications. The result showed that the doses of vermicompost fertilizer of 400 g per plant combined with M. bracteata as cover crop gave the highest value on the leaf number and stem diameter. In contrast, the best treatment for leaf chlorophyll content was 200 g per plant vermicompost without LCC planting. Thus, the application of vermicompost combined with the planting of Mucuna bracteata cover crop on young cinchona plants is strongly recommended.Keywords: Cinchona ledgeriana, Mucuna bracteata, organic fertilizer, plant growth. AbstrakTanaman kina (Cinchona ledgeriana Moens) merupakan tanaman obat-obatan penting yang sangat berpotensi untuk dikembangkan sebagai obat bahan alam. Tanaman ini dapat tumbuh baik di dataran tinggi. Penanaman kina di wilayah marjinal memerlukan berbagai modifikasi seperti pemberian tanaman penutup tanah (LCC) untuk mempertahankan kelembaban tanah dan pemenuhan nutrisi melalui pemupukan. Tujuan dari penelitian ini untuk melihat pengaruh kombinasi dari penggunaan Mucuna bracteata sebagai LCC dan dosis pupuk kascing pada pertumbuhan tanaman kina belum menghasilkan di wilayah marjinal. Penelitian ini dilakukan sejak September 2019 hingga Maret 2020 di kebun percobaan Ciparanje, Fakultas Pertanian, Universitas Padjadjaran. Rancangan percobaan menggunakan rancangan acak kelompok (RAK) dengan 12 perlakuan yang terdiri dari kombinasi tanaman penutup tanah (LCC) yaitu Mucuna bracteata dan pupuk kascing (0 g, 200 g, 400 g, 600 g, 800 g and 1000 g) per tanaman yang diulang empat kali. Hasil penelitian menunjukkan dosis pupuk kascing 400 g/tanaman yang dikombinasikan dengan Mucuna bracteata menghasilkan jumlah daun dan diameter batang tertinggi dibandingkan perlakuan lainnya. Sedangkan 200 g pupuk kascing tanpa LCC merupakan perlakuan dengan nilai klorofil daun tertinggi. Berdasarkan hasil tersebut, penggunaan pupuk kascing yang dikombinasikan dengan Mucuna bracteata sebagai LCC dapat meningkatkan pertumbuhan tanaman kina belum menghasilkan.Kata Kunci: Cinchona ledgeriana, Mucuna bracteata, pupuk organik, pertumbuhan tanaman.